In-plane aligned assemblies of 1D-nanoobjects : recent approaches and applications - Hu, Hebing (2020)
One-dimensional (1D) nanoobjects have strongly anisotropic physical properties which are averaged out and cannot be exploited in disordered systems. The goal of the present review is to describe the current methods for preparing macroscopic composite films in which the long axis of individual 1D-nanoobjects is more or less parallel to the x,y-plane of the substrate as well as to each other (alignment direction). Such structures are generally described as in-plane anisotropic and many of their physical properties show minima or maxima parallel to the alignment direction. Optical polarizers are a typical class of such materials, but anisotropic materials properties can enhance the performance of devices and materials over many length scales in various disciplines of materials science including electronic devices, environmental sensors, energy saving and energy generation applications, plasmonic devices, Surface-Enhanced Raman Scattering (SERS) and biological applications. The reviewed alignment methods fall into two categories: techniques in which all nanoobjects remain in the x,y-plane and the in-plane densities and alignment are controlled; and techniques allowing building complex architectures in which each stratum of multilayered or stacked films may differ in chemical nature or alignment direction or both. This review serves a purpose to provide a platform to inspire new alignment approaches with improved assembly quality and upscaling potential and new applications with enhanced performance by alignment.